Iron Chemistry Made Easy: Chiral N2P2 Ligands for Asymmetric Catalysis - Bigler, Raphael; Huber, Raffael; Mezzetti, Antonio (Synlett, 2016)
In this account, we summarize our recent work on the preparation of C2-symmetric macrocyclic N2P2 and open-chain NPPN iron(II) complexes. The investigation of these new ligand classes is enabled by the development of a synthetic route to the key enantiopure, P-stereogenic dialdehyde. Macrocyclization with a diamine affords N2P2 ligands, the iron(II) complexes of which are highly active and selective precatalysts for the asymmetric transfer hydrogenation of ketones. Condensation with monoamines affords open-chain NPPN ligands, of which the highly azaphilic iron(II) complexes are tested in the asymmetric Strecker reaction.1 Introduction1.1 Iron Complexes: The Issue of Stability1.2 Open-Chain PNNP Ligands1.3 Goals and Motivation2 N2P2 Macrocycles2.1 The Key C2-Symmetric Synthon2.2 C2-Symmetric N2P2 Macrocycles3 Macrocyclic Iron(II) Complexes3.1 Bis(acetonitrile) N2P2 Complexes3.2 Bis(acetonitrile) (NH)2P2 Complexes3.3 Enlarging the Toolbox: Isonitrile (CNR) Ligands3.4 Asymmetric Transfer Hydrogenation Fe/N2P24 Chiral Open-Chain NPPN Ligands4.1 Synthesis of Bis(acetonitrile) Complexes4.2 Complex Derivatization4.3 Asymmetric Transfer Hydrogenation Fe/NPPN4.4 Strecker Reaction of Azomethine Imines5 Conclusion and Outlook
Keywords: macrocycles; iron; asymmetric catalysis; hydrogen transfer; alcohols